Comparative diversity in glochidia of Australasian freshwater mussels - Klunzinger, Michael W.; Jones, Hugh A.; Humphrey, Christopher L.; Melchior, Michele; Raadik, Tarmo A.; Treby, Sarah; Chandler, Lisa; Sheldon, Fran (Frontiers in Environmental Science, 2023)
Most freshwater mussels have larvae (glochidia in Unionidae, Margaritiferidae and Hyriidae) that are parasitic on fishes. This study describes and compares the diversity of glochidia among 17 species of Australasian Hyriidae. Here, scanning electron microscopy was used to illustrate shell morphology, while patterns of diversity in size, shape and morphological characteristics were analysed quantitatively and qualitatively with Principal Component, Linear Discriminant, and Multiple Correspondence Analyses to separate species with varying degrees of discrimination. Results showed shell lengths ranged from 50 to 390 μm. Shape varied, from sub-oval to sub-triangular, bilaterally symmetrical to scalene, and hook morphology varied from unicuspid, bicuspid, tricuspid or complex with varying length and structure. Unique observations of this study include the consistent variation in glochidial release mechanisms among Australian subfamilies and New Zealand genera. Hyridellini species and Echyridella aucklandica (Gray, 1843) are released either freely or as ‘mesoconglutinates’ (presumed brood lures), whereas Velesunioninae and Echyridella menziesii (Gray, 1843) release glochidia in ‘amorphous mucous conglutinates’. Hyridellini predominantly occur within perennially flowing rivers of coastal south-eastern Australia with generally low turbidity, whereas the Velesunioninae occur more typically in slower flowing, intermittent waters, many prone to extended periods of high turbidity. Thus, where Hyridellini occurs, mesoconglutinates as visual brood lures may be a more efficient mechanism for infesting host fishes than the passive infestation strategy typical of velesunionine species frequenting more turbid waters. Finally, this study presents systematic descriptions of glochidia and a provisional key for identification of Australasian hyriid glochidia, making an important contribution to the current understanding of taxonomy and life history traits, both critical for hyriid conservation.